Downhill turn techniques and performance in cross-country skiing: Associations with mechanical and physical parameters - Bucher, S. (2012)
Downhill turns in cross-country skiing are performed in widely varying conditions. In order to perform well, i.e. effectively utilize potential energy and accelerating forces from the leg push-off, skiers must adapt their entrance velocity, the trajectories throughout the turns and the employment of techniques. The aims of this study were to characterize the main techniques utilized in downhill turns among female elite cross-country skiers and to examine how downhill turn performance is influenced by technique distribution, mechanical parameters and the skiers` maximal strength and power. Twelve female elite cross-country skiers performed six highly standardized, subsequent turns using a freely chosen technique. The subjects were continuously monitored by a high-end real time kinematics GNSS and one camcorder. From here, the measured trajectory was used for calculating total and intersection times, velocity and energy dissipation at each point of observation. Video analysis was used to determine the distribution of techniques. In the laboratory, maximal isometric squats and counter-movement jumps were performed to characterize the athletes` peak strength and power. Side-stepping, skidding and ploughing were identified as the three main techniques utilized in different phases of downhill turns in cross-country skiing. The faster skiers in downhill turns preferred skidding to ploughing in decelerating parts of the turns and showed an earlier initiation and overall greater use of the accelerating side-stepping technique (all p < 0.05). Furthermore, better performance in the turns was related both to higher velocity and shorter trajectory (all p < 0.01). Peak force, time to peak force and rate of force development in a countermovement jump were most strongly correlated with performance (all p < 0.05). Overall, the current study identified side-stepping, skidding and ploughing as the main techniques distributed in cross-country skiing downhill turns. Better skiers featured a greater portion of the side-stepping technique, which was initiated earlier in the turn and at a higher velocity. These technical patterns lead to higher velocities at shorter trajectories throughout the turn, in association with higher peak leg power.